(untitled) (Journal of Hama University, 2022)
A trial was carried out to study the effect of including different levels of wet or fermented feed by using Synbiotic in the daily feed of broilers on some productivity indicators of broilers, 3000 one day-old chicks of commercial meat line(ROSS) were used in the trial. Then they are distributed to ten groups, each group containing 300 chicks with three replications: (A) negative witness, without addition to their feed or water, (B) positive control with Synbiotic to its dry daily Feed until the end of the experiment (W) 25% wet feed + 75% dry feed (W1) 50% wet feed + 50% dry feed (W2) 75% wet feed + 25% dry feed (W3) 100% wet feed until the end of the experiment (F) 25% fermented Feed by using symbiotic + 75% dry feed without symbiotic (F1) 50% Fermented feed by using symbiotic+50% dry feed without symbiotic (F2)75% Fermented feed by using symbiotic + 25%dry feed without symbiotic (F3) 100% Fermented feed by using symbiotic. the experiment continued until 43 days of age. The results of the study showed a highly significant (P<0.01) in RBC, hematocrit, and hemoglobin for the two groups F2, F3 compared to the negative control group, and it was significantly (P<0.05) compared to the positive control, A significant decrease (P<0.01) was observed for the wet groups compared to the rest of the groups, and an improvement in the serum indicators was observed when using fermented feed, as the TP increased and cholesterol and blood sugar decreased.